2022
DOI: 10.1158/0008-5472.can-21-0614
|View full text |Cite
|
Sign up to set email alerts
|

BRAF Inhibitors Reprogram Cancer-Associated Fibroblasts to Drive Matrix Remodeling and Therapeutic Escape in Melanoma

Abstract: The tumor stroma and its cellular components are known to play an important role in tumor response to treatment. Here, we report a novel resistance mechanism in melanoma that is elicited by BRAF inhibitor (BRAFi)–induced noncanonical activation of nuclear β-catenin signaling in cancer-associated fibroblasts (CAF). Treatment with BRAFi leads to an expanded CAF population with increased β-catenin nuclear accumulation and enhanced biological properties. This CAF subpopulation is essential for melanoma cells to pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 48 publications
0
30
1
Order By: Relevance
“…To uncover the underlying mechanism behind the effects of PDPN(+) CAFs in promoting cell migration, we analyzed the differentially upregulated genes in mCAFs compared with nonCAFs using transcriptome data (Figure 3A). Among the top five genes, POSTN has been previously reported to be closely related to CAFs 17–19 . The upregulation of POSTN expression in PDPN(+) CAFs compared to PDPN(‐) CAFs and NFs was further validated by immunofluorescent staining (Figure 3B).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…To uncover the underlying mechanism behind the effects of PDPN(+) CAFs in promoting cell migration, we analyzed the differentially upregulated genes in mCAFs compared with nonCAFs using transcriptome data (Figure 3A). Among the top five genes, POSTN has been previously reported to be closely related to CAFs 17–19 . The upregulation of POSTN expression in PDPN(+) CAFs compared to PDPN(‐) CAFs and NFs was further validated by immunofluorescent staining (Figure 3B).…”
Section: Resultsmentioning
confidence: 68%
“…Previous studies have demonstrated that POSTN activates FAK and AKT pathways in cancer cells during tumor development 19,20 . Thus, we aimed to determine which pathways were activated by POSTN secreted from PDPN(+) CAFs.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, CD90+ fibroblast and FAP+ fibroblast counts are significantly positively associated with progression-free survival (PFS) and overall survival (OS), whereas a-SMA+ fibroblast count is negatively associated with PFS and OS in melanoma patients treated with anti-PD1 Abs monotherapy [ 100 ]. CAFs induce resistance not only in immunotherapy but also to BRAF inhibitors in advanced melanoma [ 101 , 102 ]. Indeed, BRAF inhibitors enhance β-catenin nuclear accumulation through the induction of BRAF-CRAF heterodimerization and subsequent activation of ERK signaling in both CAFs and melanoma cells, leading to proliferation of melanoma cells [ 101 ].…”
Section: Profiles Of Tumor-infiltrating Leukocytes Determine the Char...mentioning
confidence: 99%
“…CAFs induce resistance not only in immunotherapy but also to BRAF inhibitors in advanced melanoma [ 101 , 102 ]. Indeed, BRAF inhibitors enhance β-catenin nuclear accumulation through the induction of BRAF-CRAF heterodimerization and subsequent activation of ERK signaling in both CAFs and melanoma cells, leading to proliferation of melanoma cells [ 101 ]. Berestjuk et al reported that extracellular matrix (ECM) derived from CAFs abrogate the anti-melanoma effects of BRAF/MEK inhibition in melanoma through discoidin domain receptors (DDR)1 and DDR2 phosphorylation [ 102 ].…”
Section: Profiles Of Tumor-infiltrating Leukocytes Determine the Char...mentioning
confidence: 99%
“…Moreover, BRAF inhibitors activate ERK signaling in CAFs, leading to activation of beta-catenin and the secretion of POSTN. This protein, in turn, reactivates ERK signaling in melanoma cells under BRAFi pressure, further promoting resistance ( Liu et al, 2022 ).…”
Section: Ecm and Remodeling In Therapeutic Resistancementioning
confidence: 99%